Management of anxious patients in the dental office: A literature review (Research, Society and Development, 2025)
Historically, dentistry in Brazil began in a precarious manner, being practiced by barbers without academic training. The procedures, often brutal and painful, left traumatic marks that have persisted over the years. In this context, fear and anxiety became associated with dental care, creating a negative image of the profession. Consequently, there are evident obstacles to regular dental visits, which negatively impact adherence to oral care and the overall quality of life of patients. This study aims to identify the factors that trigger dental anxiety and analyze effective strategies for managing these patients. Data collection was conducted through a systematic search of scientific articles in the databases Google Scholar, BVS, and Scielo. The results demonstrate that distress and fear in the dental office create significant barriers to oral healthcare. Given this reality, it is essential that dental professionals can recognize the signs of anxiety and adopt appropriate management strategies. Among these, both non-pharmacological and pharmacological techniques stand out, such as the use of benzodiazepines and nitrous oxide, which represent viable alternatives when applied with safety, clinical judgment, and professional responsibility. It is concluded that proper anxiety management should be seen as an integral part of dental care, transforming negative experiences into positive ones, to provide more effective services that promote well-being and oral health.